PERBANDINGAN PENINGKATAN KADAR GLUKOSA DARAH PUASA SEBELUM DAN SESUDAH PEMBERIAN MADU HUTAN DAN GULA PASIR MAHASISWA ANGKATAN 2015 FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - FANDY NOVRIAN; SITI HAJAR (JURNAL ILMIAH SIMANTEK, 2020)
At the highest levels increase after consuming food. While fasting gold content is the gold content obtained after the patientfasts for 8-10 hours. Carbohydrates that have a low glycemic index cause a slight increase in blood sugar levels, whilecarbohydrates with a high glycemic index will cause a high increase in blood glucose. Honey has a low glycemic index.To determine the increase in the amount of reserves after the honey and granulated forest in the 15th in the 2015 studentforce FK UMSU who fasts for 8 hours. This study used the True Experiment method by designing "pretest-posttest withcontrol group design" to find out the difference in increase fasting blood glucose level after given honey and granulated sugarin the 15th minute of the 2015 student force FK UMSU. This study showed an increase in blood glucose levels after theadministration of honey with a mean value of 115.91 and standard deviation of 9,731 with P values = 0,000. Increased bloodglucose levels after giving sugar with a mean value of 118.36 and standard deviation of 9.212 with P value = 0,000.The increase blood glucose levels in 2015 student force FK UMSU 15 minutes after being given honey is slightly higher thanthose given sugar.